A prática dialógica com pacientes oncológicos: experiência de acadêmicos de enfermagem - Almeida Júnior, José Jailson de (2019)
Objective: To report the experience of Nursing students in the dialogue drowingduring the data collection from a doctoral research with cancer patients from various sectors of a reference hospital in cancer treatment in the state of Amazonas. Methods: This is a descriptive study, type experience report. For methodological basis, we used the stages of Systematization of Experiments, proposed by HollidayJO. Experience Report:The experience was the result of the dialogue established at the time of application of data collection instruments to users of the treatment sectors of the Amazonas State Oncology Control Center Foundation located in Manaus, Amazonas State, by academics. Nursing School of Manaus -Federal University of Amazonas (EEM / UFAM) by participating as collaborators in a doctoral research. Conclusion:Within the dialogical process, nursing becomes a major operationalizer of communication strategies for better recovery of hospitalized individuals. This reality should be worked out in the academic context, given that the dialogue employed with patients, through practices performed still in the academy, results in the formation of a professional prepared to deal with the singularities of individuals undergoing cancer treatment